2012
DOI: 10.1016/j.ajhg.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Associations for Activated Partial Thromboplastin Time and Prothrombin Time, their Gene Expression Profiles, and Risk of Coronary Artery Disease

Abstract: Activated partial thromboplastin time (aPTT) and prothrombin time (PT) are clinical tests commonly used to screen for coagulationfactor deficiencies. One genome-wide association study (GWAS) has been reported previously for aPTT, but no GWAS has been reported for PT. We conducted a GWAS and meta-analysis to identify genetic loci for aPTT and PT. The GWAS for aPTT was conducted in 9,240 individuals of European ancestry from the Atherosclerosis Risk in Communities (ARIC) study, and the GWAS for PT was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
76
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 55 publications
15
76
2
1
Order By: Relevance
“…These results suggest that the prolonged aPTT in those with type O is partly due to low FVIII levels. A genome-wide association study showed that aPTT is significantly associated with KNG1 , HRG , F11 , F12 , and ABO genes [27] . Although ABO type cannot account for all inter-individual variations in aPTT, some of the variations in aPTT can be explained by the ABO type.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the prolonged aPTT in those with type O is partly due to low FVIII levels. A genome-wide association study showed that aPTT is significantly associated with KNG1 , HRG , F11 , F12 , and ABO genes [27] . Although ABO type cannot account for all inter-individual variations in aPTT, some of the variations in aPTT can be explained by the ABO type.…”
Section: Discussionmentioning
confidence: 99%
“…In the other research, the GWAS for APTT and PT was conducted and replicated genome-wide significant associations at KNG1, HRG, F11, F12, and ABO for APTT and identified significant associations at the F7 and PROCR/EDEM2 regions for PT. Eight genetic loci accounted for ~29% of the variance in APTT, and two loci accounted for ~14% of the variance in PT [27]. In this study, the association of APTT, PT, FIB, and TT with ITGA2B and ITGB3 SNPs was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The likely principal mechanism is a differential susceptibility to thrombosis: people of blood group O have 25% lower plasma levels of von Willebrand factor and Factor VIII, both members of the blood coagulation cascade, and SNPs defining group O are associated with less coagulable blood on standard laboratory coagulation tests. (Tang et al, 2012) Congruent with this observation, ABO genotypes are the strongest risk factor genome-wide for venous thromboembolism (Qi et al, 2010). Nevertheless, other potential mechanisms whereby the pleiotropic ABO locus could contribute to MI risk have been identified through GWAS approaches.…”
Section: Discussionmentioning
confidence: 99%